Management science, theory of constraints/optimized production technology and local optimization - Verma, R. (Omega (Oxford), 1997)
This study uses a controlled laboratory experiment to compare the performances of Management Science (MS), Theory of Constraints/Optimized Production Technology (TOC/OPT) and Local Optimization (LO) approaches to production planning. The OPT game was used as the experimental instrument. The subjects were given hint sheets based on MS, TOC/OPT and LO approaches. The results show that production planning by MS and TOC/OPT approaches improve the performance more than the LO approach. Additionally MS was found to improve the performance more than TOC. Statistical power analysis of the data suggests that the laboratory experiment had a high power and the tested approaches had a medium to large effect on performance.